The state of the Japanese state : contested identity, direction and role - McCormack, Gavan (Renaissance Books Asia Pacific series, 2018)
Gavan McCormack's latest work argues that Abe Shinzo's efforts to re-engineer the Japanese state may fail, but his radicalism continues to shake the country and have consequences not easy to predict. Its significance will be recognized by those researching contemporary world politics, international relations and the history of modern Japan.